Charm of Author intervention: Narrative Theoretical Analysis on Milan Kundera’s Works - Ma Feng (Lingua Cultura, 2008)
Article discusses the narrative of "interference" theory. The discussion with the author’s intervention and then gives a detailed and profound discussion. The author uses four ways to carry out the intervention, such as "deliberate go away, having no intention of sneaking, into the intention of the highlights, at random creative". This article talks about the creation of a detailed narrative analysis and has a further exploration about the effect of narrative. Under such theory frame and the synthesis, this article is attempting a utilization of the narrative theory to the text explanation.